Synthesis of Some Antileprotic Drugs from Some Indigenous Flora - Kataria, H.C.; Gupta, S.S. (Asian Journal of Chemistry, 2010)
In the present paper we have repprted synthesis of some antileprotic drugs from some indigenous flora